Standard gross margin for poultry - Rodica Chetroiu; Lidia Iurchevici (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 3rd Edition of the International Symposium, October 2012, Bucharest, 2012)
The standard gross margin (SGM) is the difference between the gross product (GP) of a product and the direct proportional expenditures (DPE). The standard gross margin shall be calculated on one activity unit: surface (1 ha) or per head: SGM = GP - DPE The standard gross product at poultry is calculated per kg of meat and per 1000 eggs and includes the total output value plus the supplied subsidy. Direct proportional expenditures (DPE) are expenditures that vary directly with the changes in the size of agricultural production (biological material expenditures, feeding stuffs, energy, medicine, insurance and other material expenditures). Are called variable expenditures. Fixed production expenditures such as machinery, buildings (their amortization), permanent labor expenditures, rents or variable costs such as fuel and lubricants, equipment and machinery maintenance and works contracted with third parties are not included in costs for calculation of standard gross margin SGM. The standard gross margin for poultry was calculated for an average daily gain of 45 g at broiler chickens and for an average annual output of 260 eggs / head, to laying hens. The study results show that, in relation with the variable expenditures level, is realized an economic efficiency of the activity performed, which leads to a positive and bigger standard gross margins.
Keywords: 330; standard gross margin; poultry; gross product; direct expenditures